Meningkatkan Efektivitas Arang Bakau Pada Proses Karburising Padat Baja Karbon Rendah Menggunakan Barium Karbonat - Soemowidagdo, Arianto Leman; Mujiyono, Mujiyono (Jurnal Semesta Teknika, 2009)
The effect of BaCO3 on bakau charcoal effectiveness as a carburizer for pack carburizing process was investigated. Bakau charcoal being produced from bakau trees were sifted on 30 mesh sieve. BaCO3 was then added into the bakau charcoal sieves with composition of 0, 15, 20, 25, and 30 wt %. The pack carburizing was carried out at 850 0C for 2 hours. Low-carbon steel containing 0.156 %C was used as specimen. After being carburized, all specimens were reheated at 850 0C, hold it for 5 minutes, and subsequently quenched into water at 28 oC. The result shows that BaCO3 improves bakau charcoal effectiveness as a solid media in pack carburizing proces. By adding of 20, 25 dan 30 wt % of BaCO3, it produced the case depth of 190 mm, 250 mm dan 325 mm, respectively. Martensite structure that arises on steel surface after being quenched indicates the increase of the amount of carbon atoms.Â